(untitled) (Journal of Pedagogical Inventions and Practices, 2025)
This article analyzes the pedagogical mechanisms for developing students’ professional competencies based on an integrative approach. The theoretical foundations of the concept of professional competence are revealed, and the role of emotional-value-based relationships, levels of logical and semantic thinking, as well as a creative and active learning environment aimed at enhancing the effectiveness of individual learning is substantiated in the processes of its formation and improvement. By designing the educational process on the basis of an integrative approach, the possibilities for the harmonious development of students’ professional, personal, and social competencies are demonstrated. In addition, the article highlights the factors that ensure the effectiveness of mechanisms for developing professional competencies based on pedagogical modeling